(untitled) (World Science, 2021)
The coronavirus (Covid-19) pandemic is the global health crisis of our time. Every day people lose their jobs and income. The World Health Organization estimates that 25 million jobs could be lost. The pandemic has caused serious damage to the tourism industry. International traffic statistics decreased by 74%. One of the businesses that has been severely affected by the pandemic is the hotel business. More than 75% of which suffered significant revenue cuts and 46% of hotels and restaurants had to lay off staff in full. There are 262 accommodation facilities in Imereti, where 1179 people are employed. Studies have shown that the number of employees in all hotels has been significantly reduced, while 10% of small hotels have closed altogether. Overall, from the first wave of the pandemic to the survey period, 65.8% of hotel staff were laid off (free leave was granted): small hotels reduced service staff by 71%, medium-sized hotels by an average of 65%. Hotel revenue for the first 10 months of 2020 decreased significantly compared to the same period in 2019 (reduced by 75%). It was found that due to delays caused by the coronavirus, additional financial resources were needed to save the business and 34% of the hotels applied to financial institutions. The state is trying to support small and medium-sized businesses with measures such as deferral of rent, subsidies, deferral of taxes. Quarantine zones and coveted hotels were opened in a number of hotels, which helped maintain employment and income for sector representatives and people employed in the sector.